Proveniência de depósitos albianos do grupo Itapecurú (Bacia de São Luis - Grajaú) com base em petrografia, paleocorrentes, geoquímica e idades de zircão detrítico - NASCIMENTO, Marivaldo dos Santos (Universidade Federal do Pará, 2017)
The Albian deposits comprise ca. 70% of sedimentary fill of the São Luís-Grajaú Basin, with 500 m thick in their main depocenters. The origin and sedimentary evolution of these deposits is related to the breakup of Africa and South America which led to the connection of the formerly separated Central and South Atlantic oceans, in Mesozoic time. Albian exposures in the southern border of the São Luís-Grajaú Basin, Grajaú region, represent a fluvial-deltaic succession whith six depositional environments, including: delta front (mouth) bar, distal bar/prodelta, upper shoreface/foreshore, interdistributary bay/crevasse, fluvial channel and distributary channel. They consist, mainly, of fine- to medium sandstones, as well as siltstones, mudstones and intraformational conglomerate. Palaeocurrent study, petrography and geochemistry of sandstones and heavy minerals, and detrital zircon ages were utilized to investigate the provenance of this sedimentary unit. This study was performed on sandstone samples whose modal compositions plot in the quartzarenite field indicating origin from recycled orogen and continental blocks. High proportion of quartz grains, monocrystaline and polycrystalline, as well as quartzite fragments, and rounded grains of zircon and tourmaline with a wide variety of mechanical surface textures, suggest a provenance from sedimentary rocks, and that at least part of the studied sediments are multicyclic. Chemical weathering processes is little evident as indicated by absence of solution features in these mineral grains. Therefore, the modal composition can be related to the sedimentary recycling or strong reworking on depositional environment. High CIA (Al2O3/Al2O3+K2O+Na2O+CaO*x100) values suggest transportation and recycling from sources located far away from the depositional basin, which is, in turn, consistent with a provenance from the recycled orogens and continental blocks. Based on palaeocurrent patterns and RuZi the Albian succession in the south region of the São Luís-Grajaú Basin was defined four heavy mineral zones, generically named A, B, C and D, in ascending stratigraphic order. Geochemistry of tourmaline grains indicate provenance from metapelites and metapsammites, with few contributions from granite and pegmatite. Zircon Hf patterns suggest changing of the source of these zones: Zone A is characterized by an Hf unimodal distribution, while in the Zones B, C and D, is bimodal. The staurolite shows a relatively limited amount of compositional variations. Involvement of metasediments is inferred from the presence of staurolite and kyanite in the sandstones, as well as by predominance of dravite in the tourmaline populations. Discriminant function analysis using major element compositions show that these deposits were deposited in the passive continental margin (PM). PM sediments are mainly quartz-rich, sourced from craton interiors or stable continental regions, which were deposited in intra-cratonic sedimentary basins or on passive continental margin. The Albian sediments are characterized by LREE enrichment, depletion in HREE, and negative Eu-anomaly. This REE pattern, measured to infer the provenance of sediments and their relationship with average post-Archean upper continental crust, is very consistent with this interpretation. Enriched HREE concentration in the some samples may be attributed to the presence of REE bearing heavy minerals, supported by the fact that these samples have higher concentration of Th, U and Zr, reflecting natural concentration of zircon grains. Pb-Pb geochronological analyses of 238 detrital zircon grains show a direct fingerprint of Precambrian terrains (Archean to Proterozoic) in the source. Three major zircon populations were detected: Archean (3103-2545 Ma), Paleoproterozoic (2460- 1684 Ma) and Neoproterozoic (993-505 Ma); small groups of Mesoproterozoic (1570- 1006 Ma), Paleozoic (440-540 Ma) and Mesozoic (141-314 Ma) grains are also present. The Neoproterozoic component shows an increase upwards with main peaks between 550 Ma and 650 Ma. A similar pattern is shown by the Archean interval, which exhibits a strong relative increase upwards, peaking between 2725 Ma and 2926 Ma, while Paleoproterozoic component has a distinct behavior, showing an evident decrease upwards. The potential source regions were deduced on the basis of palaeocurrent patterns and correlations of detrital zircon age from the sandstones studied with U-Pb and Pb-Pb zircon data from the basement. Our data suggest that the Albian deposits, specially those of the Zone A, were preferentially sourced from the northern and northeastern regions, including São Luís Craton, Gurupi Belt and northwestern portion of Borborema Province. Paleoproterozoic and Neoproterozoic zircon ages as those found in zircons from this zone, are very common in these basement. In contrast, the sediments of zones B, C e D were supplied from the areas located to the south, southwest and, possibly east, involving the eastern portion of the Amazonian Craton/Araguaia Belt, and Borborema Province. Metassedimentary and igneous rocks with similar zircon ages (mainly Archean) have been described in these regions. The ca. 1.0 Ga detrital zircon ages show a correspondence with the Cariris Velhos Event, widely recognized in the central portion of the Borborema Province. In summary, this study demonstrates the effectiveness of an integrated approach to provenance evaluation of Cretaceous sedimentary deposits using petrography, heavy minerals and bulk sediment chemistry, zircon ages, and palaeocurrent data.